Analisis Keragaman Komunitas Bakteri pada Lambung Madu Lebah Apis mellifera, Apis cerana, dan Tetragonula laeviceps: Analysis of Communities Bacterial Diversity on Bees Honey Stomach from Apis mellifera, Apis cerana, and Tetragonula laeviceps - Rosadela, Fitri; Rusmana, Iman; Raffiudin, Rika; Nurjanah (Jurnal Sumberdaya Hayati, 2025)
Bees are one of the pollinators that a honey producing agent as well. Honey derives from nectar that stored and procees in honey stomach. The quality of honey is determined by physical, chemical and microbes in the honey stomach as well. This study was aimed to analyze the diversity of bacterial communities (bacterial metagenome) derived from bee’s honey stomach of A. mellifera, A. cerana, and T. laeviceps using Denaturing Gradient Gel Electrophoresis (DGGE) method. Previous researches of bacterial communities are more focused on the entire digestive tract, which is not specifically in honey stomach of the bees. The diversity of bacterial communities showed differences among three bee’s species. The number one of A. cerana has the highest number of Operational Taxonomic Units (OTUs), i.e., 15 OTUs compared to the other sample. While the T. laeviceps number two show the highest percentage of OTU dominant at 59.4%. The bacterial community in bees honey stomach of A. mellifera, A. cerana, T. laeviceps the similarity of bacteria from phylum Firmicutes, Proteobacteria, Acidobacteria and Fusobacteria. Actinobacteria and Bacteroidetes phyla are found only in A. cerana honey stomach.